PERFORMANCE OF MADRASAH HEADS IN IMPROVING THE QUALITY OF LEARNING - Zulpriyadi, Fajar; Amiruddin, Amiruddin; Siregar, Astri Novia (Hijri, 2024)
The aim of this research is to determine 1) The performance of the madrasa head, 2) Efforts to improve the quality of learning, 3) The performance of the madrasa head in improving the quality of learning at Madrasah Ibtidaiyah Negeri 1 Langkat. This type of research is qualitative with case study management. Research procedures using data collection techniques were carried out using interviews, observation and documentation. The results of this research are 1) The performance of the madrasa head as an Educator, Manager, Administrator, Supervisor, Leader. 2) Efforts to improve the quality of learning at Madrasah Ibtidaiyah Negeri 1 Langkat include providing guidance, motivation, and conducting teacher evaluations. 3) The performance of the madrasa head in improving the quality of learning at Madrasah Ibtidaiyah Negeri 1 Langkat, as a supervisor of the madrasa head's supervision activities to observe the learning process directly, especially in the selection and methods, media used and student involvement in the learning process, Involving teachers to participate in education can add new insights and knowledge, so that teachers are better prepared to carry out learning. The implications of this research are that it is hoped that madrasah heads can contribute more, be creative, innovative and coordinate madrasah residents in an effort to improve the quality of learning, parties involved in cooperation can maintain and hold training by providing opportunities for all teachers to improve their competence